Improving the organisation of maternal health service delivery and optimising childbirth by increasing vaginal birth after caesarean section through enhanced women-centred care (OptiBIRTH trial): study protocol for a randomised controlled trial (ISRCTN10612254). Issue 1 (December 2015) - Clarke, Mike; Savage, Gerard; Smith, Valerie; Daly, Deirdre; Devane, Declan; Gross, Mechthild; Grylka-Baeschlin, Susanne; Healy, Patricia; Morano, Sandra; Nicoletti, Jane; Begley, Cecily
Abstract Background The proportion of pregnant women who have a caesarean section shows a wide variation across Europe, and concern exists that these proportions are increasing. Much of the increase in caesarean sections in recent years is due to a cascade effect in which a woman who has had one caesarean section is much more likely to have one again if she has another baby. In some places, it has become common practice for a woman who has had a caesarean section to have this procedure again as a matter of routine. The alternative, vaginal birth after caesarean (VBAC), which has been widely recommended, results in fewer undesired results or complications and is the preferred option for most women. However, VBAC rates in some countries are much lower than in other countries. Methods/Design The OptiBIRTH trial uses a cluster randomised design to test a specially developed approach to try to improve the VBAC rate. It will attempt to increase VBAC rates from 25 % to 40 % through increased women-centred care and women's involvement in their care. Sixteen hospitals in Germany, Ireland and Italy agreed to join the study, and each hospital was randomly allocated to be either an intervention or a control site. Discussion If the OptiBIRTH intervention succeeds in increasing VBAC rates, its application across Europe might avoid the 160, 000 unnecessary caesarean sections that occur every year at an extra direct annual cost of more than €150 million. Trial registration Current Controlled TrialsISRCTN10612254, registered 3 April 2013.